2022
DOI: 10.1371/journal.pone.0266703
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, specific, extraction-less, and cost-effective RT-LAMP test for the detection of SARS-CoV-2 in clinical specimens

Abstract: In 2019 a newly identified coronavirus, designated as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread rapidly from the epicenter in Wuhan (China) to more than 150 countries around the world, causing the Coronavirus disease 2019 (COVID-19) pandemic. In this study, we describe an extraction-less method based on reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) intended for the rapid qualitative detection of nucleic acid from SARS-CoV-2 in upper respiratory specimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Primer sets match the SARS-CoV2 Ref Seq reference genome 100% (Wuhan-Hu-1; NC 045512.1 ). In-Silico inclusivity analysis by Marino et al, [ 7 ] demonstrated primer sets to differ by one or less mutation in 99.8%, 99.8% and 99.6% (Orf1, E, and N gene respectively against 5773195 SARS-CoV-2 GISAID deposited sequences), with extremely low potential for poor primer hybridization to occur across all three primer sets. Furthermore, minimal In-Silico and wet testing cross-reactivity was observed for pathogens similar or related to SARS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primer sets match the SARS-CoV2 Ref Seq reference genome 100% (Wuhan-Hu-1; NC 045512.1 ). In-Silico inclusivity analysis by Marino et al, [ 7 ] demonstrated primer sets to differ by one or less mutation in 99.8%, 99.8% and 99.6% (Orf1, E, and N gene respectively against 5773195 SARS-CoV-2 GISAID deposited sequences), with extremely low potential for poor primer hybridization to occur across all three primer sets. Furthermore, minimal In-Silico and wet testing cross-reactivity was observed for pathogens similar or related to SARS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…During this period, a single repeat swab was requested due to inefficient sampling as identified by failure of amplification within the ACTB control reaction indicating absence of total RNA. In total, 9 RT-PCR confirmed RT-LAMP positive results from a total of 1,673 tests demonstrated a prevalence of asymptomatic infection of 0.54% (540 [7] demonstrated primer sets to differ by one or less mutation in 99.8%, 99.8% and 99.6% (Orf1, E, and N gene respectively against 5773195 SARS-CoV-2 GISAID deposited sequences), with extremely low potential for poor primer hybridization to occur across all three primer sets. Furthermore, minimal In-Silico and wet testing cross-reactivity was observed for pathogens similar or related to SARS [7].…”
Section: University Of Leicester Rt-lamp Asymptomatic Screening Progr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of amplification requires 30 min or less. The LAMP assay for SARS‐CoV‐2 has been widely used in POCT (Anurup et al, 2020 ; Garcia‐Venzor et al, 2021 ; Huang et al, 2022 ; Marino et al, 2022 ; Wei et al, 2021 ). Six primers in the LAMP assay targeting eight distinct sites of the sequence ensure sensitivity and specificity (Hardinge & Murray, 2019 ; Jiang et al, 2020 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%